Detection of Phosphorylated Alpha-Synuclein in the Muscularis Propria of the Gastrointestinal Tract Is a Sensitive Predictor for Parkinson’s Disease - Goichi Beck; Yumiko Hori; Yoshito Hayashi; Eiichi Morii; Tetsuo Takehara; Hideki Mochizuki (Parkinson's Disease)
Background. Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor and nonmotor impairments, including constipation. Lewy bodies and neurites, the pathological hallmarks of PD, are found in the enteric nervous system (ENS) as well as the central nervous system. Constipation is a well-documented premotor symptom in PD, and recent reports have demonstrated Lewy pathology in gastrointestinal (GI) tissues of PD patients prior to the onset of motor symptoms. Objective. In the present study, we assessed Lewy pathology in the GI tracts of seven PD patients who had undergone a gastrectomy, gastric polypectomy, or colonic polypectomy prior to the onset of motor symptoms in order to assess whether the presence of pathological αSyn in the ENS could be a predictor for PD. Methods. GI tissue samples were collected from control patients and patients with premotor PD. Immunohistochemistry was performed using primary antibodies against α-synuclein (αSyn) and phosphorylated αSyn (pαSyn), after which Lewy pathology in each sample was assessed. Results. In all control and premotor PD patients, accumulation of αSyn was observed in the myenteric plexus in both the stomach and colon. In 82% (18/22) of control patients, mild-to-moderate accumulation of αSyn was observed in the submucosal plexus. However, there was no deposition of pαSyn in the ENS of control patients. In patients with premotor PD, abundant accumulation of αSyn was observed in the myenteric plexus, similar to control patients. On the other hand, pαSyn-positive aggregates were also observed in the nerve fibers in the muscularis propria in all examined patients with premotor PD (100%, 3/3), while the deposition of pαSyn in the submucosal plexus was only observed in one patient (14%, 1/7). Conclusion. Our results suggest that the detection of pαSyn, but not αSyn, especially in the muscularis propria of GI tracts, could be a sensitive prodromal biomarker for PD.